AN ANALYSIS OF THE BASIC PRINCIPLES OF HIGHER TAXON NOMENCLATURE, USING EXAMPLES FROM THE BRYOZOA - Kubanin A.A. (My University, 2001)
Seven postulates and thirteen nomenclatural principles are considered. Some of these are used for taxon names at all taxonomic levels, others apply mainly to order-phylum groups. Three paradigms of nomenclature (descriptions, revision, and a type) are discussed. The priority of authorship of the following taxa is amended: family Adeonidae Busk, 1884, Cellariidae Fleming, 1828, Celleporidae Lamouroux, 1816, Cerioporidae Bronn, 1849, Frondiporidae Smitt, 1865, Hippothoidae Gray, 1848, Microporidae Gray, 1848, Tubuliporidae Blainville, 1834. The use of the name Membraniporina Ortmann, 1890 is recommended to replace Malacostega s.s. sensu d'Hondt, 1985, and the name Flustrina Smitt, 1868 to replace Neomalacostega excluding Ascophora, the name Cribrilinomorpha Kaestner, 1963 to replace Cribriomorpha and the name Celleporomorpha Johnston, 1847-for lepraliemorphous bryozoans. For nomenclatural reasons the use of the names Tubuliporida to replace Cyclostomata, and Fenestellida to replace Fenestrata is supported.